Effect of Aspirin on the Thrombelastogram of Human Blood - de Gaetano, G; Vermylen, J (Thrombosis and Haemostasis, 1973)
Thrombelastograms of both native blood and re-calcified platelet-rich plasma samples taken from subjects given a single oral dose of aspirin (1 gram) were not significantly different from the pretreatment recordings. Aspirin also did not modify the thrombelastogram when preincubated in vitro with platelet-rich plasma at concentrations inhibiting the platelet “release reaction” by collagen. Thrombelastography therefore cannot evaluate the effect of aspirin on platelet function.